Serum and Tissue Expression Levels of Leptin and Leptin Receptor Are Putative Markers of Specific Feline Mammary Carcinoma Subtypes - Gameiro, Andreia; Nascimento, Catarina; Urbano, Ana Catarina; Correia, Jorge; Ferreira, Fernando (Frontiers in Veterinary Science, 2021)
Obesity is an established risk factor for breast cancer in post-menopausal women, being associated with elevated serum levels of leptin. Although, overweight is a common condition in cat, the role of leptin and its receptor in feline mammary carcinoma remains unsettled. In this study, serum leptin and leptin receptor (ObR) levels were investigated in 58 cats with mammary carcinoma and compared with those of healthy animals, as were the expression levels of leptin and ObR in tumour tissues. The results showed that the Free Leptin Index is significantly decreased in cats with mammary carcinoma (p=0.0006), particularly in those with luminal B and HER2-positive tumours, and that these animals also present significantly lower serum leptin levels (p<0.0001 and p<0.005, respectively). Furthermore, serum leptin levels above4.17 pg/mL were associated with ulcerating tumours (p=0.0005) and shorter disease-free survival (p=0.0217). In contrast, elevated serum ObR levels were found in all cats with mammary carcinoma (p<0.0001), with levels above 16.89 ng/mL being associated with smaller tumours (p=0.0118), oestrogen receptor negative status in HER2-positive tumours (p=0.0291) and increased serum levels of CTLA-4 (p=0.0056), TNF-α (p=0.0025), PD-1 (p=0.0023) and PD-L1 (p=0.0002). In tumour samples, leptin is overexpressed in luminal B and triple-negative carcinomas (p=0.0046), whereas ObR is found to be overexpressed in luminal B tumours (p=0.0425). Altogether, our results support the hypothesis that serum levels of leptin and ObR can be used as biomarkers of specific feline mammary carcinoma subtypes, and suggests the use of leptin antagonists as a therapeutic tool, reinforcing the utility of the cat as a cancer model.